Knowledge, attitude, and practice of consumers towards “Front of Package Label” (FOPL) on food packages regarding nutrition in India - Prajapati, Arpit Chelabhai; Patel, Dr Himadri; Patel, Dr Mansi; Chaudhary, Dr. Sahilkumari; Soni, Rajvee; Soni, Saloni; Wadhwani, Vidhi (JHeS (Journal of Health Studies), 2023)
Food labels give information about the elements of the food and can help people make healthy diet choices. Food labels are potential tools for improving the dietary patterns of populations and could change dietary behavior. The aims of this study were to assess the knowledge and attitude of consumers related to FOPL, evaluate the practices of consumers regarding FOPL, and identify consumers' purchasing preferences for packaged food. A cross-sectional study was conducted at selected supermarkets in Gandhinagar city using a convenient sampling method. A total of 500 participants were selected from 4 supermarkets (125 participants were selected from each supermarket). Exit interviews were done through pretested, semi-structured questionnaires. Out of 500 participants, 79% read food labels, but only 15% knew about FOPL. 88.2% of people noticed manufacturing and expiration dates on packaged food. Only 50% of the participants thought that FOPL contained nutritional information. 49.4% knew that FOPL was present on the front side of package food. 90% of people consume Namkeen food as packaged food. 59.4% thought that FOPL helped them choose healthier food, and 73% thought it should be mandatory on all food packages. Education level is significantly related to knowledge and information on the FOPL (P = 0.0001). Education programmes about nutrition labeling and how to read nutrition labels properly must be done to increase consumers' awareness, knowledge, and understanding of the importance of nutrition labeling information. It can be an effective means of helping consumers make healthier food choices and prevent NCDs.